Infant Receipt of Health Care Services during the 2016−2017 Zika Virus Outbreak in Puerto Rico - D'Angelo, Denise; Smith, Ruben A.; Salvesen von Essen, Beatriz; Kortsmit, Katherine; Ellington, Sascha; Galang, Romeo; Hernández-Virella, Wanda; Shulman, Holly; Vargas-Bernal, Manuel; Warner, Lee (Puerto Rico Health Sciences Journal, 2022)
Objective: To assess the receipt of health care services among live-born infants of women with and without evidence of Zika virus (ZIKV) infection while pregnant during the 2016–2017 ZIKV outbreak in Puerto Rico. Methods: We used data from the Pregnancy Risk Assessment Monitoring System–Zika Postpartum Emergency Response study telephone surveys to examine maternal reports of the receipt of health care services by infants born in Puerto Rico from August through December 2016 and November through December 2017. Evidence of ZIKV infection was ascertained from the infant’s birth certificate or was self-reported in the survey. Results: Fourteen percent of women in 2016 and 9% in 2017 had evidence of ZIKV infection during pregnancy. Most infants of women with evidence of ZIKV received the recommended health care services in 2016 and 2017, respectively, including a hearing test (91% vs. 92%), developmental assessment (90% vs. 92%), and an eye exam (74% vs. 70%); fewer received a head scan (45% vs. 36%) and evaluation for physical therapy (17% vs. 10%). From 2016 to 2017, the proportion of infants having a personal doctor increased for all infants; for infants of women without evidence of ZIKV infection, receiving hearing, developmental, and eye assessments increased. Conclusion: Most infants of women with evidence of ZIKV infection during pregnancy received the recommended hearing and developmental assessments during the ZIKV outbreak. Experiences with increasing service capacity during the ZIKV outbreak can be evaluated to inform the response to future emergencies that affect maternal and child health.